A three-layer composite structure collagen-based artificial skin and its preparation method
By adopting a three-layer composite structure artificial skin, including a silicone membrane layer and a double-layer porous scaffold layer, the problems of poor mechanical properties of existing collagen-based artificial skin and the residual toxicity of crosslinking agents are solved, and high biocompatibility and Excellent repair effect of full-thickness skin defects.
Patent Information
- Application Number
- CN202210860210.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-21
AI Technical Summary
The existing collagen-based artificial skin is difficult to simulate the structure of the full-layer skin, has poor mechanical properties, and there is cytotoxicity problem in the residual crosslinking agent, making it difficult to effectively repair the full-layer skin defect.
Artificial skin with three-layer composite structure, including silicone membrane layer and double-layer porous scaffold layer. The double-layer porous scaffold layer consists of collagen membrane layer and collagen sponge layer, prepared by procedural lyophilization and gradient heating methods, with high biocompatibility and good mechanical properties.
It achieves good mechanical properties and biocompatibility of collagen-based artificial skin, promotes trauma repair, avoids cytotoxicity caused by the residue of crosslinking agents, and has excellent effect on repairing skin defects in the whole-thickness.
Smart Images

Figure CN115518201B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a three-layer composite structure collagen-based artificial skin and a preparation method thereof. Background Art
[0002] The skin is the largest organ in the human body and can effectively protect the body's tissues and organs from damage by external factors. The skin can provide important physiological functions for the human body, including temperature regulation, hydration, perspiration, and the synthesis of vitamin D. Severe damage to the skin will lead to damage to the body's key functions, leading to complications and even death in severe cases. When a large area of skin is damaged due to accidents or diseases such as burns, scalds, and skin ulcers, the skin cannot repair itself and needs to be treated through skin transplantation. The key to treating skin defects is to promote wound healing and prevent complications caused by disorders of the internal environment and microbial infections. In traditional treatments for skin defects, the source of autologous skin grafts is limited, while allogeneic skin grafts have problems such as immune rejection, disease transmission, and ethics.
[0003] The use of tissue engineering to construct artificial skin with similar structure and function to normal skin has attracted much attention in the repair of large-area full-thickness skin defects. Collagen-based artificial skin has the advantages of good tissue regeneration ability, high biocompatibility, low cytotoxicity, and low immune rejection, and has great development potential in the field of tissue engineering artificial skin. Single-layer collagen-based artificial skin is difficult to simulate the structure of full-thickness skin, and has disadvantages such as poor mechanical properties and residual toxicity of cross-linking agents. Therefore, it is of great significance to construct artificial skin with good mechanical properties and biocompatibility that can repair full-thickness skin defects. Invention patent CN104984407B discloses a tissue engineering artificial skin and a preparation method thereof, wherein the artificial skin comprises an epidermis and a dermis, wherein the epidermis is collagen or a blend of collagen and chitosan, and the dermis is collagen or a blend of collagen and chitosan, hyaluronic acid, chondroitin sulfate, alginate or polyvinyl alcohol, and there is a risk of poor mechanical strength; invention patent CN106853263A discloses a double-layer artificial skin and a preparation method thereof, wherein the upper layer is a silicone rubber film with a surface modified with nano-silver, and the lower layer is a collagen composite film, and the upper and lower layers are bonded together by silicone gel.
[0004] The inventor unexpectedly discovered a method during the research process, by which a double-layer scaffold layer including a collagen membrane layer and a collagen sponge layer is prepared in one step, and a collagen-based artificial skin with a three-layer composite structure is prepared using the double-layer scaffold layer. The artificial skin has a structure similar to that of normal skin, good mechanical properties and high biocompatibility, and the collagen membrane plays a good secondary barrier role in tissue repair. The artificial skin has an excellent repair effect on full-thickness skin defects and has broad application prospects in the fields of skin medicine, tissue repair products, etc. Summary of the invention
[0005] The specific plan is as follows:
[0006] The primary purpose of the present invention is to provide a three-layer composite structure collagen-based artificial skin, the artificial skin includes a silicone membrane layer and a double-layer porous scaffold layer, the double-layer porous scaffold layer includes a collagen membrane layer-collagen sponge layer, and the three-layer structure from top to bottom is respectively a silicone membrane layer-collagen membrane layer-collagen sponge layer, the silicone membrane layer has a thickness of 0.3-1mm, the collagen membrane layer has a thickness of 0.4-10μm, the collagen sponge layer has a thickness of 1.5-5mm, and the total thickness is 1.8-7mm.
[0007] Preferably, the porosity of the collagen sponge layer is 76-90%, the collagen sponge layer has a three-dimensional porous structure, the average pore size is 60-150 μm, and the collagen membrane layer has no pores.
[0008] Preferably, the double-layer porous scaffold layer is prepared from the following raw materials by weight through programmed freeze-drying and gradient temperature increase: 83-93wt% collagen and 7-17wt% mucopolysaccharide;
[0009] The freeze drying process is as follows: the mold is placed in a freeze dryer, cooled from room temperature to -35°C, and kept frozen at a constant temperature for 8-24 hours;
[0010] The gradient heating method is to heat the material from -35°C to -20°C at a heating rate of 5°C / h; heat it from -20°C to -15°C at a heating rate of 0.78°C / h and keep it warm for 1h; heat it from -15°C to -5°C at a heating rate of 2°C / h; heat it from -5°C to 25°C at a heating rate of 7.5°C / h and keep it warm and vacuum dry for 16h.
[0011] Preferably, the collagen is type I collagen; and the mucopolysaccharide is chondroitin sulfate and / or hyaluronic acid.
[0012] A second object of the present invention is to provide a method for preparing the artificial skin, comprising the steps of:
[0013] (1) using acetic acid solution to dissolve and prepare collagen and mucopolysaccharide solution respectively, and under stirring, slowly adding the mucopolysaccharide solution dropwise to the collagen solution according to the proportion, and stirring evenly;
[0014] (2) vacuum degassing the solution prepared in step (1) to remove the bubbled part; evenly spreading the material in a polyethylene mold, freeze-drying, and gradually increasing the temperature to obtain a double-layer porous scaffold material;
[0015] The freeze drying process is as follows: the mold is placed in a freeze dryer, cooled from room temperature to -35°C, and kept frozen at a constant temperature for 8-24 hours;
[0016] The gradient heating method is to heat the material from -35°C to -20°C at a heating rate of 5°C / h; from -20°C to -15°C at a heating rate of 0.78°C / h, and keep warm for 1h; from -15°C to -5°C at a heating rate of 2°C / h; from -5°C to 25°C at a heating rate of 7.5°C / h, and keep warm and vacuum dry for 16h;
[0017] (3) thermally dehydrogenating the double-layer porous scaffold material obtained in step (2) for 24 hours, cooling to room temperature, double cross-linking, washing, and freeze-drying to obtain a double-layer porous scaffold layer;
[0018] (4) Mix the A and B components of silica gel in a ratio of 1:1, stir, and vacuum degas. Spread the mixed silica gel on the collagen membrane layer of the double-layer porous scaffold layer obtained in step (3), and solidify the silica gel to obtain artificial skin.
[0019] Preferably, the double cross-linking in step (3) is formed by cross-linking the double-layer porous scaffold layer by a physical method, a chemical method or a combination of the two methods.
[0020] Preferably, the cross-linking described in step (3) is to immerse the double-layer porous scaffold material in an EDC-NHS solution prepared in a 40% ethanol solution, cross-link for 12 hours in a 37°C constant temperature box, the EDC content is 50 mmol / L, the molar ratio of EDC / NHS is 5:1, and the washing is first washed twice with 40% ethanol and then washed 3-4 times with ultrapure water.
[0021] The third object of the present invention is to provide the use of the artificial skin in the preparation of tissue repair products.
[0022] The fourth object of the present invention is to provide a tissue repair product made from the artificial skin.
[0023] Preferably, the tissue repair product is a hernia repair patch, a female pelvic floor dysfunction disease repair system, an artificial rotator cuff, a dura mater repair patch, a spinal meningeal repair patch, a pericardial patch, an artificial dental membrane, a trauma repair product, a burn repair product, a fistula wound repair product, a packing product or an organ wound repair product.
[0024] The beneficial effects of the present invention are:
[0025] (1) The present invention provides a double-layer porous scaffold layer prepared by a programmed freeze-drying and gradient temperature increase method, wherein the double-layer porous scaffold layer is a collagen membrane layer-collagen sponge layer, including a collagen membrane layer with a dense structure and a collagen sponge layer with a uniform network structure;
[0026] (2) The present invention utilizes the double-layer porous scaffold layer to prepare a three-layer artificial skin, which has good mechanical properties and swelling and dissolution properties, and provides the function of transporting nutrients and metabolites for wound repair; has good tensile strength and is suitable for suturing with the body; has good resistance to enzymatic hydrolysis and biodegradability, and can prevent wound retraction in the early stage of wound repair, and undergoes biodegradation after wound repair, avoiding the problems of secondary debridement and material residue;
[0027] (3) The double-layer porous scaffold material of the present invention has high biocompatibility and low cytotoxicity, which overcomes the cytotoxicity problem caused by the cross-linking agent residue in the artificial skin prepared by glutaraldehyde cross-linking; it has a good internal pore structure, provides a good scaffold for cell growth, and promotes cell proliferation and adhesion;
[0028] (4) The collagen membrane layer of the present invention can play a good role in interlayer isolation, effectively preventing the outer silicone material from penetrating into the dermis, thereby better protecting the stability of the internal environment of the artificial skin dermis and promoting cell infiltration and growth;
[0029] (5) The artificial skin of the present invention is non-pyrogenic and has good blood compatibility, indicating that it has good biosafety;
[0030] (6) The artificial skin described in the present invention has an excellent repair effect on full-thickness skin defects and has broad application potential in the fields of dermatology, tissue repair products, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Flow chart of collagen-based artificial skin preparation
[0032] Figure 2 SEM characterization of the double-layer porous scaffolds prepared by different freezing procedures
[0033] Figure 3 Structural characterization of collagen-based artificial skin
[0034] (a) Macroscopic observation of the lower dermis layer of artificial skin, (b) Macroscopic observation of artificial skin folding, (c) Artificial skin preserved in PBS solution, (d) and (g) SEM characterization of the three-layer structure of artificial skin, (e) and (h) SEM characterization of the porous sponge of artificial skin, (f) SEM characterization of the collagen membrane layer, (i) SEM characterization of the double-layer porous scaffold layer (collagen sponge layer and collagen membrane layer).
[0035] Figure 4 Physicochemical properties of the dermis layer of collagen-based artificial skin
[0036] (a) Fourier transform infrared analysis (FTIR), (b) cross-linking degree, (c) dissolution rate, (d) swelling, (e) tensile strength, and (f) resistance to enzymatic degradation.
[0037] Figure 5 Biocompatibility and bioactivity of collagen-based artificial skin
[0038] (a) Cytotoxicity, (b) cell proliferation, (c) cell adhesion, (d) live cell / dead cell staining, (e) cell growth morphology in the extract, (f) cell growth morphology on the material, and (g) cell migration in the material.
[0039] Figure 6 Biological safety of collagen-based artificial skin
[0040] (a) Pyrogen test, (b) Hemolysis test.
[0041] Figure 7 Wound repair performance of collagen-based artificial skin
[0042] (a) Wound surface observation, (b) HE staining, (c) Masson staining. DETAILED DESCRIPTION
[0043] The following examples further illustrate the specific technical solutions of the present invention in detail, so as to facilitate further understanding of the present invention by those skilled in the art, but do not constitute a limitation on the rights thereof.
[0044] Example 1: Preparation of three-layer collagen-based artificial skin
[0045] Preparation method 1:
[0046] Use acetic acid solution to dissolve and prepare type I collagen and chondroitin sulfate mother solution respectively. Under stirring, add chondroitin sulfate mother solution drop by drop slowly to type I collagen solution, and add appropriate amount of acetic acid solution to dilute the solution so that the final concentration of collagen content is 5mg / ml and chondroitin sulfate content is 1mg / ml, and then stir to make the solution uniform. The solution prepared in the above steps is vacuum defoamed in a vacuum drying oven to remove the bubble part above. The material is evenly spread in a polyethylene mold, and in a freeze dryer, the temperature is increased gradually and the program is freeze-dried to obtain a double-layer porous scaffold material. The material is moved to a vacuum drying oven and thermally dehydrogenated at 110℃. After the material is naturally cooled to room temperature, it is immersed in EDC-NHS solution (EDC content in EDC-NHS solution is 50mmol / L, and the molar ratio of EDC / NHS is 5:1) for cross-linking. After that, the residual cross-linking agent of the material is cleaned and freeze-dried again to obtain a double-layer porous scaffold layer. At room temperature, the A and B components of silica gel were uniformly mixed in a ratio of 1:1, stirred at 300 rpm for 10 min, and vacuum degassed. The mixed silica gel was then evenly spread on the collagen membrane layer of the double-layer porous scaffold layer, and the silica gel was cured at 60°C for 3 h. After sterilization, the collagen-based artificial skin was immersed in PBS solution for storage.
[0047] Preparation method 2:
[0048] Use acetic acid solution to dissolve and prepare type I collagen and chondroitin sulfate mother solution respectively. Under stirring, add the chondroitin sulfate mother solution drop by drop slowly to the type I collagen solution, and add an appropriate amount of acetic acid solution to dilute the solution so that the final concentration of collagen is 5 mg / ml, and the ratio of collagen to chondroitin sulfate is 12.5:1, and then stir to make the solution uniform. The solution prepared in the above steps is vacuum defoamed in a vacuum drying oven to remove the bubble part above. The material is evenly spread in a polyethylene mold, and in a freeze dryer, the temperature is increased gradually and the program is freeze-dried to obtain a double-layer porous scaffold material. The material is moved to a vacuum drying oven and thermally dehydrogenated at 110°C. After the material is naturally cooled to room temperature, it is immersed in an EDC-NHS solution (the EDC content in the EDC-NHS solution is 50 mmol / L and the molar ratio of EDC / NHS is 5:1) for cross-linking. After that, the residual cross-linking agent of the material is cleaned and freeze-dried again to obtain a double-layer porous scaffold layer. At room temperature, the A and B components of silica gel were uniformly mixed in a ratio of 1:1, stirred at 300 rpm for 10 min, and vacuum degassed. The mixed silica gel was then evenly spread on the collagen membrane layer of the double-layer porous scaffold layer, and the silica gel was cured at 60°C for 3 h. After sterilization, the collagen-based artificial skin was immersed in PBS solution for storage.
[0049] Preparation method 3:
[0050] The method for preparing the artificial skin comprises the following steps:
[0051] (1) Use 0.5M acetic acid solution to dissolve and prepare type I collagen and chondroitin sulfate mother solution. Under stirring, slowly add the chondroitin sulfate mother solution drop by drop into the type I collagen solution, and add an appropriate amount of 0.5M acetic acid solution to dilute the solution to a final concentration of 5mg / ml type I collagen and 0.67mg / ml chondroitin sulfate. Then stir the solution to make it uniform for 12 hours at a speed of 1200rpm. The above process is completed in an ice water bath with a temperature not higher than 4°C.
[0052] (2) Degas the material in step (1) in a vacuum drying oven and remove the bubbles on top. Spread the material evenly in a polyethylene mold with a thickness of 3-5 mm. Freeze-drying: Place the mold in a freeze dryer, cool it from room temperature to -35°C, and freeze it at a constant temperature for 10 hours. In the subsequent vacuum freeze-drying process, the temperature is increased in a gradient manner: the material is heated from -35°C to -20°C at a heating rate of 5°C / h; the material is heated from -20°C to -15°C at a heating rate of 0.78°C / h, and kept warm for 1 hour; the material is heated from -15°C to -5°C at a heating rate of 2°C / h; the material is heated from -5°C to 25°C at a heating rate of 7.5°C / h, and kept warm and vacuum dried for 16 hours to obtain a double-layer porous scaffold material CCS.
[0053] (3) Move the material in step (2) to a preheated vacuum drying oven at 110°C and perform thermal dehydrogenation treatment for 24 hours. After the material is naturally cooled to room temperature, the DHT-treated material DCCS is obtained. Immerse in an EDC-NHS solution prepared with a 40% ethanol solution (the EDC content in the EDC-NHS solution is 50 mmol / L, and the molar ratio of EDC / NHS is 5:1) for cross-linking, and cross-link in a 37°C constant temperature oven for 12 hours. After that, clean the residual cross-linking agent in the material, first wash it twice with 40% ethanol, then wash it 3-4 times with ultrapure water, and freeze-dry it again to obtain a double-layer porous scaffold EDCCS after double cross-linking treatment.
[0054] (4) At room temperature, the A and B components of the silica gel were uniformly mixed in a ratio of 1:1, stirred at 300 rpm for 10 min, and vacuum degassed. The mixed silica gel was then evenly spread on the collagen membrane layer of the double-layer porous scaffold layer (3), and the silica gel was cured at 60°C for 3 h. After sterilization, the collagen-based artificial skin TLCCS was immersed in PBS solution for storage.
[0055] (5) After sterilization, the collagen-based artificial skin was immersed in a PBS solution for storage. The preparation flow chart is shown in FIG. Figure 1 shown.
[0056] Comparative Example 1:
[0057] The other operation steps are the same as those in Example 1. The freeze-drying procedure in step (2) is to place the mold in a freeze dryer, cool it from room temperature to -20°C, and freeze it at a constant temperature for 10 hours.
[0058] Comparative Example 2:
[0059] The other operation steps are the same as those in Example 1. The freeze-drying procedure in step (2) is to place the mold in a freeze dryer, cool it from room temperature to -80°C, and freeze it at a constant temperature for 10 hours.
[0060] Comparative Example 3:
[0061] The other operating steps are the same as those in Example 1. The freeze-drying procedure in step (2) is to pre-freeze at -35°C for 10 h (the same as in Example 1). Then, the mold is placed in a freeze dryer. During the subsequent vacuum freeze-drying process, the temperature is linearly increased from -35°C to 25°C at a heating rate of 5°C / h. The material is kept in vacuum drying for 32 h to obtain a linearly increased freeze-dried sponge material.
[0062] Comparative Example 4:
[0063] The other operating steps are the same as those in Example 1. The freeze-drying procedure in (2) is performed at -35°C for 10 h pre-freezing (the same as in Example 1), and then the mold is placed in a common freeze dryer. In the subsequent vacuum freeze-drying process, freeze-drying is performed at room temperature and vacuum dried for 44 h to obtain a sponge material freeze-dried at room temperature.
[0064] SEM characterization of the double-layer porous scaffolds prepared by different freezing procedures Figure 2 shown. Figure 2 A1-A4 are the scaffold materials prepared in comparative example 1, which are freeze-dried at -20°C, and the bottom layer is a collagen sponge with a mesh structure, but the mesh is not uniform, and the collagen membrane layer formed on the top layer is incomplete, with a large number of pores; B1-B4 are the scaffold materials prepared in Example 1, and the bottom layer is a collagen sponge with a uniform mesh structure, and the collagen membrane layer formed on the top layer is dense, smooth and has no pores; C1-C4 are the scaffold materials prepared in comparative example 2, which are freeze-dried at -80°C, and the collagen sponge layer formed on the bottom layer has no uniform mesh structure, and the top layer does not form a complete collagen membrane layer; D1-D4 are the scaffold materials prepared in comparative example 3, and the bottom layer is a porous sponge, and the top layer does not form a collagen membrane; E1-E4 are the scaffold materials prepared in comparative example 4, and the bottom layer is a porous sponge, and the top layer does not form a collagen membrane. Therefore, linear heating and room temperature freeze-drying cannot prepare a double-layer scaffold material with a collagen membrane on the top layer.
[0065] The macrostructure and SEM microstructure of the collagen-based artificial skin prepared in Example 1 are as follows: Figure 3As shown in Figure 3(a). The sponge layer of the artificial skin is a milky white uniform solid, as shown in Figure (a); the silicone membrane layer has a good interface bonding with the collagen double-layer scaffold, as shown in Figure (b); the artificial skin is immersed in PBS solution and is a milky white translucent solid, as shown in Figure (c). The SEM images of the artificial skin are shown in Figures 3(d) and (g), forming a three-layer composite structure of silicone membrane layer-collagen membrane layer-collagen sponge layer, and having good interface stability; the SEM images of the porous scaffold layer are shown in Figures 3(e) and (h), forming a double-layer structure of collagen membrane-sponge, with a natural transition of the double-layer interface and a dense and smooth collagen membrane layer; the SEM images of the sponge layer are shown in Figures 3(f) and (i), showing an interconnected porous structure with uniformly distributed pores and an average pore size of 92.44μm. This pore structure can improve the water absorption capacity of the artificial skin and provide beneficial growth conditions for cells.
[0066] Example 2: Characterization of the physical and chemical properties of the double-layer porous scaffold layer
[0067] 1. Sample preparation.
[0068] EDCCS: a double-layer porous scaffold layer prepared by double cross-linking. The specific preparation method is as shown in Example 1.
[0069] Control: Scaffold material prepared by traditional glutaraldehyde cross-linking. The specific preparation method is as follows:
[0070] The steps for preparing a mixed solution of type I collagen and chondroitin sulfate are the same as those in Example 1. After preparing the mixed solution, maintain the rotation speed at 1200rpm. Take a 50% glutaraldehyde solution, dilute it with a 0.5M acetic acid solution, and slowly add it dropwise into the solution to make the final concentration of glutaraldehyde 0.5%. After the addition is completed, withdraw the ice water bath, keep stirring, cross-link at room temperature for 4 hours, and vacuum degas in a vacuum drying oven to remove the bubbled part above. Spread the material evenly in a polyethylene mold, place the mold in a freeze dryer, and the gradient pre-freezing and heating procedures are the same as in Example 1 to obtain a traditional glutaraldehyde-prepared scaffold material.
[0071] ECCS: scaffold material prepared by traditional EDC-NHS cross-linking. The specific preparation method is as follows:
[0072] The steps for preparing a mixed solution of type I collagen and chondroitin sulfate are the same as those in Example 1. After preparing the mixed solution, maintain the rotation speed at 1200 rpm. Take EDC-NHS solution, prepare it using 0.5M acetic acid solution, and slowly add it dropwise to the solution in (1) to make the final concentration of EDC-NHS 50 mmol / L, the molar ratio of EDC / NHS 5:1, and adjust the pH of the solution to 5.5. After the addition is completed, remove the ice water bath, keep stirring, cross-link at room temperature for 12 hours, and vacuum degas in a vacuum drying oven to remove the bubble part above. Spread the material evenly in a polyethylene mold, place the mold in a freeze dryer, and the gradient pre-freezing and heating procedures are the same as in Example 1 to obtain a traditional EDC-NHS cross-linked scaffold material.
[0073] DCCS: Scaffold material prepared by thermal dehydrogenation cross-linking:
[0074] The steps of preparing the mixed solution of type I collagen and chondroitin sulfate are the same as those in Example 1, and then thermal dehydrogenation cross-linking is adopted to prepare the scaffold material;
[0075] CCS: Double-layer porous scaffold material prepared without cross-linking treatment:
[0076] The steps for preparing the mixed solution of type I collagen and chondroitin sulfate are the same as those in Example 1.
[0077] 2. Fourier Transform Infrared Analysis (FTIR)
[0078] A small piece of collagen-based artificial skin sample was cut into pieces in a mortar, ground and mixed evenly with KBr, pressed into a transparent thin sheet in a tablet press, and its infrared scanning spectrum was measured using a NEXUS 670 infrared spectrometer with a scanning range of 4000 to 400 cm-1, and the data was analyzed.
[0079] 3. Cross-linking degree
[0080] 5 mg of uncrosslinked and crosslinked double-layer porous scaffold layers were added to 1 mL of 4% (w / v) NaHCO3 solution for 30 minutes. Then 1 mL of freshly prepared 0.5% (v / v) TNBS deionized water was added and incubated in a 40°C water bath for 2 hours. 3 mL of 6M hydrochloric acid was added to terminate the reaction and incubated at 60°C for 90 minutes to dissolve the collagen. The mixture was diluted with 5 mL of deionized water and cooled to room temperature. The control (blank sample) was carried out according to the above procedure except that hydrochloric acid was added before the addition of TNBS. 300 μL of each solution was transferred to a 96-well plate and the absorbance was recorded at 345 nm using a microplate spectrophotometer (SynergyTM 2, BioTek, USA). The degree of crosslinking CD (%) of the material was calculated by the following formula.
[0081]
[0082] Where ODc is the absorbance of the cross-linked double-layer porous scaffold layer; ODn is the absorbance of the uncross-linked layer; and ODb is the absorbance of the blank control group.
[0083] 4. Determination of dissolution rate
[0084] Weigh a small amount of double-layer scaffold material and dry it in a dryer to constant weight, then weigh the initial weight M1 (g) of the material in a 10mL centrifuge tube and add ultrapure water. Preheat the 37°C constant temperature incubator for 30 minutes, place the materials in order, and oscillate continuously at a constant temperature for 24 hours at 220rpm. After centrifugation, freeze-dry the remaining material, dry it in a dryer to constant weight, and weigh the final weight M2 (g). The dissolution loss rate D (%) can be calculated according to formula 2-2. CCS, DCCS and Control are used as reference controls.
[0085]
[0086] 5. Swelling properties
[0087] Weigh the material mass M0 (g), put it into a certain volume of deionized water, ensure that the water can completely immerse the material, and place it in a 37°C constant temperature water bath. Weigh the mass M of the infiltrated material at a certain time interval t (g) Wipe off excess water on the surface of the material with filter paper before weighing. Calculate the swelling ratio SR at different time intervals according to formula 2-3.
[0088]
[0089] 6. Tensile strength
[0090] Cut the material into a 50×20mm rectangle, measure its thickness with a vernier caliper at room temperature, and then use a universal material testing machine to measure its tensile mechanical properties, set the tensile speed parameter to 60mm / min, record the material's width W (mm), thickness d (mm), and load F (N) at break. Calculate the material's tensile strength Rm (KPa) by the formula.
[0091]
[0092] 7. Evaluation of in vitro degradability
[0093] After the samples soaked in deionized water and then freeze-dried were balanced in a dryer for 24 hours, the mass M1 (g) of 10 ml centrifuge tubes was weighed one by one. After adding the samples into the centrifuge tubes, the initial mass of the samples and the mass of the centrifuge tubes and M2 (g) were weighed again. The above materials were numbered.
[0094] Deionized water was used to prepare a 0.05 mol / L sodium phosphate buffer solution (i.e., PBS buffer solution, pH 7.4). Type IV collagenase was weighed, and a solution was prepared and diluted to 0.5 U / ml of type IV collagenase solution using PBS solution.
[0095] Add 0.5U / ml of type IV collagenase solution to the numbered sample centrifuge tubes, seal with sealing film, and perform in vitro degradation experiments on a constant temperature shaking shaker at 37°C and 220rpm. Take out 3 portions at 1, 4, 7, 14, 21, and 28 days, centrifuge each time, and carefully wash with deionized water 3 times to ensure that there are no enzymes and PBS solution components remaining in the material. Then store the samples in a -80°C refrigerator, and freeze-dry them in a freeze dryer after the experiment. After storing in the dryer for 24 hours, weigh the mass Wt (g). Calculate the mass degradation rate MD (%) (Mass Degradation Percentage, MD) according to the formula.
[0096]
[0097] The physical and chemical properties of the double-layer porous scaffold layer are characterized as follows Figure 4 The FTIR characterization of the porous scaffold layer prepared by dual crosslinking of DHT and EDC-NHS is shown in Figure 4 As shown in (a), the characteristic absorption peaks of amide I, II, and III indicate that the collagen in the double-crosslinked porous scaffold layer maintains a complete triple helical structure. Figure 4 As shown in (b), the cross-linking degree of the DHT cross-linked scaffold material DCCS is 34.7%, the cross-linking degree of the EDC-NHS cross-linked scaffold material ECCS is 31.5%, and the cross-linking degree of the double cross-linked scaffold material EDCCS is 79%, indicating that the double cross-linking of DHT and EDC-NHS can significantly improve the cross-linking degree of the scaffold material. The dissolution rate of the porous scaffold layer is shown in Figure (c). The dissolution rate of CCS is as high as 46.8%, the dissolution rates of DHT-cross-linked DCCS and GA-cross-linked Control are 18.9% and 17.9%, respectively, while the dissolution rate of the double cross-linked EDCCS is 15.9%, indicating that the spatial structure of EDCCS maintains good stability, which is beneficial to the infiltration and migration of cells during wound repair. The swelling of the porous scaffold layer, such as Figure 4 As shown in (d), CCS reaches swelling equilibrium in about 2 hours, and cross-linked scaffold materials DCCS, EDCCS and Control reach swelling equilibrium in about 6 hours. The final swelling ratio of uncross-linked CCS is only 33, DHT cross-linked DCCS and GA cross-linked Control are 72 and 58 respectively, while the double cross-linked EDCCS can reach 95, indicating that EDCCS has good swelling properties, can provide a moist internal environment for wound repair, and can absorb wound exudate.
[0098] The tensile strength of the porous scaffold layer is Figure 4 As shown in (e), the tensile strength of uncrosslinked CCS is poor, and the tensile strength is only 30.96 KPa; the tensile strength of crosslinked DCCS and EDCCS is increased to 40.33 KPa and 50.78 KPa respectively; compared with CCS, DCCS and Control, double crosslinked EDCCS has good tensile strength and is suitable for suturing with the body. Figure 4 As shown in (f), in a PBS solution containing collagenase, the uncrosslinked CCS was almost completely degraded on the first day, with a mass degradation rate MD of 86.27%; the mass degradation rate MD of the GA-crosslinked Control on the 28th day was 62.44%, and the mass degradation rate MD of the double-crosslinked EDCCS on the 28th day was 40.37%, indicating that the double-crosslinked EDCCS has good anti-enzymatic ability and biodegradability, can prevent wound retraction in the early stage of wound repair, and the internal pore structure can provide a suitable growth environment for cells, and biodegrade after wound repair, avoiding the problems of secondary debridement and material residue, which is more conducive to skin wound repair and regeneration. These results show that the double-layer porous scaffold layer EDCCS has good mechanical properties, swelling properties, stability and biodegradability.
[0099] Example 3: Biological activity of collagen-based artificial skin with three-layer composite structure
[0100] 1. Preparation of Collagen-based Artificial Skin
[0101] Use acetic acid solution to dissolve and prepare type I collagen and chondroitin sulfate mother liquor respectively. Under stirring, add chondroitin sulfate mother liquor dropwise and slowly to type I collagen solution, and add appropriate amount of acetic acid solution to dilute the solution so that the final concentration of collagen content is 88wt% and the chondroitin sulfate content is 12wt%, and then stir to make the solution uniform. The solution prepared in the above steps is vacuum defoamed in a vacuum drying oven to remove the bubble part above. The material is evenly spread in a polyethylene mold, and in a freeze dryer, the temperature is increased gradually and the program is freeze-dried to obtain a double-layer porous scaffold material. The material is moved to a vacuum drying oven and thermally dehydrogenated at 110℃. After the material is naturally cooled to room temperature, it is immersed in EDC-NHS solution (EDC content in EDC-NHS solution is 50mmol / L, and the molar ratio of EDC / NHS is 5:1) for cross-linking. After that, the residual cross-linking agent of the material is cleaned and freeze-dried again. At room temperature, the A and B components of silica gel were uniformly mixed in a ratio of 1:1, stirred at 300 rpm for 10 min, and vacuum degassed. The mixed silica gel was then evenly spread on the collagen membrane layer of the double-layer porous scaffold layer, and the silica gel was cured at 60°C for 3 h. After sterilization, the collagen-based artificial skin was immersed in PBS solution for storage.
[0102] In the following experiments, the double-cross-linked double-layer porous scaffold layer is represented as "EDCCS", the traditional glutaraldehyde prepared scaffold material is represented as the control group "Control", the type I collagen prepared scaffold material is represented as "Col", the three-layer composite structure collagen-based artificial skin is represented as "TLCCS", and the collagen-based artificial skin without the collagen membrane layer is represented as "TLCCS-".
[0103] 2. Cytotoxicity
[0104] Under sterile conditions, sterilize the materials under ultraviolet light for 48 hours. Seal the materials in DMEM high-glucose culture medium containing 10% bovine serum at an extraction concentration of 2 mg / ml, extract them at 220 rpm in a 37°C constant temperature shaker for 24 hours to obtain the material extract for use. Inoculate 100 μl of fibroblast suspension into a 96-well plate and place it in a constant temperature and humidity incubator at 37°C for 24 hours. When the cells are completely attached to the wall and stretched, aspirate the culture medium, wash twice with PBS solution, add 100 μl of each material extract, and add 100 μl of DMEM high-glucose culture medium containing 10% bovine serum to the control group. After culturing in the incubator for 24 hours, 48 hours, and 72 hours, stain with CCK-8 dye. The original culture medium in the 96-well plate was aspirated, washed three times with PBS, and then CCK-8 dye diluted to 10% with DMEM culture medium was added, incubated in a 37°C constant temperature and humidity incubator for 1 hour, and the absorbance at a wavelength of 450nm was measured using an enzyme marker. The cytotoxicity of the material was graded according to the 24h cell survival rate, which can be divided into 5 levels: level 0 (cell survival rate ≥ 100), level 1 (80≤cell survival rate ≤ 99), level 2 (50≤cell survival rate ≤ 79), level 3 (30≤cell survival rate ≤ 49), and level 4 (0≤cell survival rate ≤ 29). The material cytotoxicity level is 0 or 1, which is qualified; the cytotoxicity level is 2, and the material should be comprehensively evaluated in combination with the cell morphology; the cytotoxicity level is 3 to 5, which is unqualified.
[0105] 3. Live and dead cell staining imaging
[0106] Digest the L929 fibroblasts in the culture dish with trypsin and count the cells. Inoculate 1 ml of fibroblast suspension into the laser confocal culture dish, place it in a constant temperature and humidity incubator at 37°C, and culture for 24 hours. When the cells are completely attached to the wall and stretched, aspirate the culture medium, wash twice with PBS solution, add 1 ml of each material extract, and change the extract every three days. When cultured for 1, 4, and 7 days, stain with Hoechst33342 / PI dye to observe the effects of different extracts on the cells. Live cells (yellow-green fluorescence) and dead cells (red fluorescence) were detected under a laser confocal microscope using 490 nm excitation, and dead cells (red fluorescence) were observed using 545 nm.
[0107] 4. Cell Proliferation
[0108] 100 μl of fibroblast suspension was inoculated into a 96-well plate and placed in a constant temperature and humidity incubator at 37°C for 24 hours. When the cells are completely attached to the wall and stretched, the culture medium was aspirated, washed twice with PBS solution, and 100 μl of each material extract was added. The extract was replaced every three days. 100 μl of DMEM high-glucose culture medium containing 10% bovine serum was added to the control group and replaced every three days. CCK-8 dye was used for staining when cultured for 1, 4, and 7 days, respectively. Aspirate the original culture medium in the 96-well plate, wash 3 times with PBS, and then add CCK-8 dye diluted to 10% with DMEM culture medium, incubate in a constant temperature and humidity incubator at 37°C, and use an enzyme marker to measure the absorbance at a wavelength of 450nm.
[0109] 5. Cell growth morphology in the extract
[0110] Digest the L929 fibroblasts in the culture dish with trypsin and count the cells. Inoculate 1 ml of fibroblast suspension into the laser confocal culture dish and culture for 24 hours. When the cells are completely attached to the wall and stretched, aspirate the culture medium, wash twice with PBS solution, add 1 ml of each material extract, and after 4 days of culture, use Hoechst 33258 (Ex / Em=360nm / 465nm) and phalloidin-tetramethylrhodamine isothiocyanate (Ex / Em=540nm / 570nm) dyes to observe the effects of different extracts on cell morphology, and replace the extract every three days.
[0111] 6. Cell Adhesion
[0112] Under sterile conditions, collagen sponges and porous double-layer scaffold materials of the same volume and thickness were sterilized under ultraviolet light for 48 hours and placed in 24-well plates for standby use. The control group was a blank well plate group. The L929 fibroblasts in the culture dish were digested with trypsin and the cells were counted. 500 μl of fibroblast suspension was inoculated into the above 12-well plate and placed in a constant temperature and humidity incubator at 37 ° C for 4 and 8 hours respectively. The original culture medium was aspirated and washed with PBS solution 3 times, and the control group was not washed with PBS solution. The total deoxyribonucleic acid of the adherent cells was determined by Hoechst 33258 solution to quantitatively compare the ability of the materials to adhere to cells. The fluorescence intensity at the excitation wavelength of 360 nm and the emission wavelength of 465 nm was measured using an enzyme marker, and each material was measured in parallel 3 times. Among them, the blank group was DMEM culture medium, the cell adhesion rate of the control group was set to 100%, and the cell adhesion rate of the remaining materials was the percentage relative to the control group.
[0113] 7. Cell growth morphology on materials
[0114] Under sterile conditions, a 3mm thick EDC cross-linked porous double-layer scaffold material was placed in a 6-well plate, 1ml 75% ethanol solution was added, soaked for 1h, replaced with 75% ethanol solution, soaked again for 1h, and repeated 3 times. The ethanol solution was aspirated, and sterilized ultrapure water was used to soak for 1h, replaced with new sterilized ultrapure water, and repeated 3-5 times for thorough cleaning. The material was placed in a laser confocal culture dish with the collagen membrane layer facing down. It was naturally dried in a clean bench. 500μl of fibroblast suspension was inoculated into the laser confocal culture dish, which was placed at a constant temperature and humidity of 37℃ for 8h, and then 500μl of DMEM complete culture medium was added, and the culture medium was replaced every three days. After culturing in the incubator for 4d, Hoechst 33258 (Ex / Em=360nm / 465nm) and phalloidin-tetramethylrhodamine isothiocyanate (Ex / Em=540nm / 570nm) dyes were used to observe the effects of different extracts on cell morphology. Fluorescence observation was performed under a laser confocal microscope. The cell nucleus (blue fluorescence) was observed using 360 nm excitation, and the cytoplasm (red fluorescence) was observed using 540 nm excitation.
[0115] 8. Growth morphology of cells inside artificial skin
[0116] Under sterile conditions, the sterilized collagen matrix was placed in a 6-well plate. 500 μl of fibroblast suspension was inoculated into the artificial skin, and then 500 μl of DMEM complete culture medium was added, and it was placed in a constant temperature and humidity culture at 37°C. The culture medium was replaced every three days. The above materials were fixed with paraformaldehyde solution for more than 24 hours on days 3 and 7, and then routinely embedded in paraffin, and the sections were stained with hematoxylin-eosin (HE staining).
[0117] The biological activity results of the collagen-based artificial skin are as follows Figure 5 As shown in Figure 2, L929 fibroblasts were used in the experiment. The cytotoxicity results of the extracts of the double-layer porous scaffold material are shown in Figure 2. Figure 5 (a), cell proliferation as Figure 5 (b), live cell / dead cell imaging Figure 5 (d) Cell growth morphology Figure 5 As shown in (e), the double-layer scaffold material EDCCS has no cytotoxicity, and cells can proliferate in large quantities in the material extract and are in a good stretching state. The cell adhesion results of the double-layer porous scaffold layer are shown in Figure 5 (c), it has good cell adhesion ability; the morphology of cells on the porous scaffold material is as follows Figure 5As shown in (f), cells can adhere and proliferate on the material, maintain a good long spindle shape, and tend to grow toward the inner layer structure, which is beneficial to the adhesion and migration of cells during wound repair. The cell migration results of the collagen-based artificial skin with a three-layer composite structure are shown in Figure 5 As shown in (g), cells can successfully migrate into the double-layer porous scaffold material and proliferate and grow on the sponge layer; compared with the control group without collagen membrane layer, the collagen membrane layer can effectively prevent the outer layer of silicone material from penetrating into the sponge layer, and can play the role of interlayer isolation, better protect the stability of the dermis environment of the artificial skin, and promote cell infiltration and growth. These results show that the collagen-based artificial skin has good biocompatibility and bioactivity, and can effectively promote cell adhesion, proliferation and migration.
[0118] Example 4: Biological safety of collagen-based artificial skin with three-layer composite structure
[0119] 1. Preparation of Double-layer Porous Scaffold
[0120] Use acetic acid solution to dissolve and prepare type I collagen and chondroitin sulfate mother liquor respectively. Under stirring, add the chondroitin sulfate mother liquor drop by drop to the type I collagen solution slowly, and add an appropriate amount of acetic acid solution to dilute the solution so that the final concentration of collagen is 83-93wt% and the chondroitin sulfate content is 6-16wt%, and then stir to make the solution uniform. The solution prepared in the above steps is vacuum defoamed in a vacuum drying oven to remove the bubble part above. The material is evenly spread in a polyethylene mold, and in a freeze dryer, the temperature is increased gradually and the program is freeze-dried to obtain a double-layer porous scaffold material. The material is moved to a vacuum drying oven and thermally dehydrogenated at 110°C. After the material is naturally cooled to room temperature, it is immersed in an EDC-NHS solution (the EDC content in the EDC-NHS solution is 50mmol / L and the molar ratio of EDC / NHS is 5:1) for cross-linking. After that, the residual cross-linking agent of the material is cleaned and freeze-dried again. In this experiment, the double-crosslinked double-layer porous scaffold layer was recorded as "EDCCS", and the traditional glutaraldehyde-prepared scaffold material was used as the control group (Control) for comparison.
[0121] 2. Pyrogen test
[0122] Preparation of test solution: The dermis layer of the collagen-based artificial skin and the dermis layer of the control group material were immersed in 0.9% sodium oxide injection solution at (37±1)℃ for (48±2)h, and heated to 38℃ in a water bath before injection.
[0123] Preparation of the experiment: 3 New Zealand white rabbits, weighing 2.0-3.4 kg, of either sex, measure and record the rectal temperature, measure 8 times, 30 minutes each time, and the rabbits with the highest and lowest body temperatures not exceeding 0.4°C are qualified.
[0124] According to the provisions of the national standard GB / T 16886.11-2011 "Biological Evaluation of Medical Devices Part 11: Systemic Toxicity Test", and the provisions of 1142 Pyrogen Test Method of Part IV of the 2015 edition of the Pharmacopoeia of the People's Republic of China, the rabbit method was used to evaluate the collagen-based artificial skin and determine the pyrogenicity of the collagen-based artificial skin. The validity of the test results is determined by the following criteria: among the three rabbits in the initial test, the body temperature rise is less than 0.6℃, and the total temperature rise of the three rabbits is less than 1.3℃; or among the five rabbits in the retest, no more than one rabbit has a body temperature rise of 0.6℃ or higher, and the total body temperature rise of the eight rabbits in the initial and retests is 3.5℃ or lower than 3.5℃, which can be judged as qualified.
[0125] Test and record the body temperature of rabbits: stabilize the rabbits with a fixture, measure the body temperature once every 30 minutes before the test solution is injected, and the difference between the two temperatures shall not exceed 0.2℃. If it exceeds, the average of the two temperatures shall be taken as the normal body temperature of the rabbit. Within 15 minutes of measuring the normal body temperature, inject the test solution of the test sample warmed to 38℃ through the ear vein, with a dose of 10mL / rabbit. After the injection, measure and record the body temperature once every 30 minutes, for a total of 6 times. The highest temperature among the 6 times minus the normal temperature is the temperature increase of the rabbit. Calculate the total temperature increase of the 3 rabbits. If the 6 temperatures are all lower than the normal temperature, the temperature increase is calculated as 0℃ when it is a negative value.
[0126] 3. Hemolysis Experiment
[0127] (1) Weigh a certain amount of double-layer porous scaffold material, rinse it with physiological saline for 3 times, add a certain amount of physiological saline at a ratio of 0.05 g / mL, incubate it at 37°C for 1 h, and prepare a material extract.
[0128] (2) Take 1 mL of fresh rabbit blood, add 5 mL of 0.1 mg / mL (heparin sodium / normal saline) anticoagulant and dilute. Centrifuge at 2500 rpm for 10 min to obtain red blood cells. Wash the red blood cells five times with 2 mL of normal saline, and then take 10 mL of normal saline to dilute the red blood cells.
[0129] (3) Take 0.2 mL of diluted red blood cells and add 0.8 mL of physiological saline (negative control group), 0.8 mL of deionized water (positive control group), and 0.8 mL of material extract, mix well, set up 3 parallel samples for each group, and incubate them in a 37°C water bath for 1 hour. All samples were allowed to stand at room temperature for 3 hours. Finally, the suspension was centrifuged at 3000 rpm for 10 minutes, and the supernatant was taken and transferred to 100 μL per well of a 96-well plate. The absorbance was measured by an ELISA reader at a wavelength of 575 nm. The hemolysis rate (HR%) was calculated according to the following formula.
[0130]
[0131] The biological safety of the collagen-based artificial skin is as follows Figure 6 As shown. Using 0.9% sodium chloride injection as the blank group, the double-layer porous scaffold layer EDCCS and the control group double-layer porous scaffold material were subjected to pyrogen test, as shown Figure 6 As shown in (a), the total increase in the body temperature of the rabbit within 3 hours was 0.1℃, 0.2℃, and 0.9℃, respectively, which was lower than 1.3℃, indicating that the material test liquids were not pyrogenic. Figure 6 As shown in (b), the hemolysis rate is 0.82%, which is significantly lower than the national standard, indicating that the double-layer porous scaffold material has good blood compatibility. These results show that the collagen-based artificial skin is non-pyrogenic and has good blood compatibility, indicating that it has good biological safety.
[0132] Example 5. Wound healing performance of collagen-based artificial skin with three-layer composite structure
[0133] 1. Construction and treatment of full-thickness skin defect model in SD rats
[0134] SD male rats weighing 150-200g were selected, and 10% chloral hydrate was used for intraperitoneal anesthesia, and the rats were anesthetized at a dose of 0.3ml / 100g body weight. All surgical operations were performed in a sterilized room. Use a shaver to remove the hair on the back of the rat, wash it with 0.9% sodium chloride injection, use a depilatory cream to remove the remaining hair, and then use 0.9% sodium chloride injection to wash it, wipe off the residual moisture and pay attention to the warmth of the rat. Use iodine to disinfect the exposed skin on the back, use a 15ml centrifuge tube to draw a circular area with a diameter of 1.5cm on the upper part of the back, use surgical scissors to completely remove the full-thickness skin, create a circular full-thickness skin defect, deep to the fascia, and stop bleeding. The blank group had no external dressing material on the defect wound; the experimental group had a three-layer composite structure collagen-based artificial skin on the defect wound; the control group had an external application of the control group artificial skin on the defect wound. The wound was sutured with No. 5 silk sewing thread at the edge, and all groups were then covered with 1 layer of sterile vaseline gauze and 3 layers of ordinary sterile gauze to wrap the wound, and fixed with elastic bandages and zinc oxide tape. The experimental animals were fed in single cages to avoid animals licking paper wounds. The feeding conditions of SD rats were observed every day and the wound materials were checked for shedding.
[0135] 2. Evaluation of artificial skin in repairing full-thickness skin defects in SD rats
[0136] The wound surface was photographed on the 7th, 10th, 14th, 18th, 21st and 25th days after surgery, and 4 animals in each group were killed. The wound edge tissue and granulation tissue were obtained, fixed with 10% formaldehyde by volume, embedded in conventional paraffin, and the sections were stained with hematoxylin-eosin (HE staining) and Masson's trichrome staining.
[0137] The effect of the collagen-based artificial skin in repairing full-thickness skin defects is as follows Figure 7 (a) As shown. On the 7th day after surgery, the wound scabs formed. The scab area of the experimental group was smaller, the color was lighter and the surface was smooth, indicating that the experimental group recovered well; the wound of the blank group was bright red, the exposed area was larger than that of other groups, the wound surface showed obvious bleeding, and there was infection and redness and swelling at the edge. On the 10th day after surgery, the skin defect healed further and the scab area decreased. On the 14th day after surgery, most of the skin defects in the experimental and control groups had healed, and only a small area of scabs existed in the center, and hair grew on the new skin around. Compared with the control group, the scabs in the experimental group were smaller and the healing was better than that of the control group. The scabs in the blank group were larger. On the 18th day after surgery, the scabs in the experimental group basically fell off, and new hair appeared around the wound; the control group and the blank group still had a small area of scabs, indicating that the experimental group was significantly better than the control group and the blank group in promoting wound healing. On the 21st day after surgery, the wound of the experimental group was basically healed, and the skin in the center of the original wound was light white with a small amount of light pink. On the 25th day after surgery, the wounds in the experimental group were completely healed, the new skin had a smooth surface and good color, no obvious hyperplasia, and hair growth increased significantly; the control group still had a small area of new thin skin in the center of the wound, which was light pink; the unhealed wounds in the blank group were significantly larger than those in the other groups. In summary, the experimental group can significantly promote wound healing and has a good wound repair effect.
[0138] HE staining of the wound surface of the full-thickness skin defect model Figure 7 (b) As shown. In the early stage of wound healing (1w), the wound surface of the blank group was sunken downward, while there was no obvious sunken phenomenon in the experimental group and the control group. The inflammatory reaction was severe, and the blood and exuded collagen in the wound quickly coagulated to form a clot. The surface of the clot dried and gradually formed a scab. In the middle stage of wound healing (2w), new tissue was visible in all groups, and there were a large number of inflammatory cells and fibroblasts in the wound. The skin appendages of the experimental group migrated to the inner layer, and obvious epidermal tissue regeneration appeared above the granulation tissue. In the late stage of wound healing (3w), the epithelial tissue keratinization was obvious, the skin appendages were renewed faster, and the structure was close to normal skin tissue. HE staining results showed that the experimental group was faster in structural remodeling than other groups.
[0139] Masson staining of the wound surface of the full-thickness skin defect model Figure 7(c) As shown. In the early stage of wound healing, the dermis of the blank group was thin, while the experimental group and the control group had partial collagen expression accompanied by abundant microvessels. In the middle stage of wound healing, a large number of collagen fibers were expressed in the wound of the experimental group. The collagen fibers tended to be regularly arranged, and the fiber bundles were thicker. The control group also had collagen fibers expressed but the arrangement was loose. In the late stage of wound healing, the upper epidermis of the experimental group was obviously keratinized, and the collagen was densely arranged. The results of Masson staining showed that the expression of collagen fibers in the experimental group was better than that in other groups.
[0140] The repair effect of the three-layer composite collagen-based artificial skin was systematically evaluated using the full-thickness skin defect wound model on the back of SD rats. In gross observation, the wound of the experimental group healed completely in 25 days, and the surface of the new skin was smooth without obvious hyperplasia, indicating that the collagen-based artificial skin effectively promoted the healing of the full-thickness skin defect wound. HE staining results showed that the artificial skin could promote the structural remodeling of the wound and was beneficial to the repair of the full-thickness skin tissue. Masson staining results showed that the artificial skin significantly promoted the expression of collagen fibers, which was beneficial to the regeneration of collagen fibers in the dermis of the wound. Therefore, collagen-based artificial skin has excellent repair ability for full-thickness skin defects.
[0141] In summary, the present invention provides a double-layer porous scaffold layer prepared by a programmed freeze-drying and gradient temperature increase method, wherein the double-layer porous scaffold layer is a collagen membrane layer-collagen sponge layer, including a collagen membrane layer with a dense structure and a collagen sponge layer with a uniform network structure; the present invention utilizes the double-layer porous scaffold layer to prepare a three-layer artificial skin, which has good mechanical properties and swelling and dissolution properties, and provides a function of transporting nutrients and metabolites for wound repair; has good tensile strength, and can be suitable for suturing with the body; has good resistance to enzymolysis and biodegradability, can prevent wound retraction in the early stage of wound repair, and undergoes biodegradation after wound repair, avoiding the problems of secondary debridement and material residue; the double-layer porous scaffold layer of the present invention is a kind of artificial skin with a three-layer structure, which has good mechanical properties and swelling and dissolution properties, and can transport nutrients and metabolites for wound repair; has good tensile strength, and can be suitable for suturing with the body; has good resistance to enzymolysis and biodegradability, can prevent wound retraction in the early stage of wound repair, and undergoes biodegradation after wound repair, avoiding the problems of secondary debridement and material residue; The porous scaffold material has high biocompatibility and low cytotoxicity, and overcomes the cytotoxicity problem caused by the crosslinking agent residue in the artificial skin prepared by glutaraldehyde crosslinking; it has a good internal pore structure, provides a scaffold for cell growth, and promotes cell proliferation and adhesion; the collagen membrane layer described in the present invention can play a good interlayer isolation role, effectively preventing the outer layer of silicone material from penetrating into the dermis, thereby better protecting the stability of the internal environment of the dermis of the artificial skin and promoting cell adhesion and growth; the artificial skin described in the present invention has no pyrogenicity and good blood compatibility, indicating that it has good biosafety; the artificial skin has an excellent repair effect on full-thickness skin defects, and has great application potential in the fields of skin medicine, tissue repair products, etc.
Claims
1. A method for preparing a three-layer composite structure collagen-based artificial skin, characterized in that: The steps include: (1) Dissolve collagen and mucopolysaccharide solution respectively using acetic acid solution and prepare the solution. Add the mucopolysaccharide solution dropwise to the collagen solution according to the proportion under stirring and stir evenly. (2) vacuum degassing the solution prepared in step (1) to remove the bubbled part; evenly spreading the material in a polyethylene mold, freeze-drying, and gradually increasing the temperature to obtain a double-layer porous scaffold material; The program freeze-drying is carried out by gradient temperature increase, the mold is placed in a freeze dryer, cooled from room temperature to -35 °C, and kept at a constant temperature for 8-24 hours; the material is heated from -35 °C to -20 °C at a heating rate of 5 °C / h; the material is heated from -20 °C to -15 °C at a heating rate of 0.78 °C / h, and kept warm for 1 hour; the material is heated from -15 °C to -5 °C at a heating rate of 2 °C / h; the material is heated from -5 °C to 25 °C at a heating rate of 7.5 °C / h, and kept warm for vacuum drying for 16 hours; (3) subjecting the double-layer porous scaffold material obtained in step (2) to thermal dehydrogenation treatment, cross-linking, and freeze-drying to obtain a double-layer porous scaffold layer; (4) Mix the A and B components of silica gel in a ratio of 1:1, stir, and vacuum degas. Spread the mixed silica gel onto the collagen membrane layer of the double-layer porous scaffold layer obtained in step (3), and solidify the silica gel to obtain artificial skin.
2. The preparation method according to claim 1, characterized in that The cross-linking described in step (3) is to immerse the double-layer porous scaffold material in an EDC-NHS solution prepared in an ethanol solution, cross-link at a constant temperature, with an EDC content of 50 mmol / L and an EDC / NHS molar ratio of 5:
1.
3. A three-layer composite collagen-based artificial skin prepared by the preparation method according to claim 1 or 2.
4. Use of the artificial skin as claimed in claim 3 in preparing a product for tissue repair.
5. A tissue repair product made from the artificial skin according to claim 3.
6. The tissue repair product according to claim 5, characterized in that: The tissue repair product is a hernia repair patch, an artificial rotator cuff, a dura mater repair patch, a spinal meningeal repair patch, a pericardial patch, an artificial dental membrane, a trauma repair product, a burn repair product, a fistula wound repair product, a packing product or an organ wound repair product.
Citation Information
Cited By
High-strength collagen rotator cuff patch and preparation method thereof
CN122376854A
High-strength collagen rotator cuff patch and method of making same
CN122376854B
